Liver Abscess Caused by Pannonibacter phragmitetus: Case Report and Literature Review - Wang, Mingxi; Zhang, Xia; Jiang, Tao; Hu, Shaohua; Yi, Zhengjun; Zhou, Yajun; Ming, Desong; Chen, Shicheng (Frontiers in Medicine, 2017)
Background: Bacterial hepatic abscess is a common occurrence in developing countries, which is mostly caused by Klebsiella pneumoniae and E. coli. Pannonibacter phragmitetus, is a Gram-negative alkalitolerant bacillus that exists in the natural environment. Human infection by this bacterium is rare, with only four cases reported. Method: We presented one of these cases with a bacterial liver abscess by a ploymicrobial infection involving P. phragmitetus and Streptococcus oralis, with P. phragmitetus being the predominate isolate. Result and Discussion: Our strain of P. phragmitetus was resistant to more antibiotics than the other reported two strains. This case further verified the infectivity of P. phragmitetus.